Kualitas Pelayanan Pembuatan Tanda Izin Masuk Daerah Keamanan Terbatas atau Kartu Pas Orang di Unit Penyelenggara Bandar Udara Tjilik Riwut Palangka Raya: Quality of Service in Making a Limited Security Entry Permit or Person Pas Pas in the Unit of Tjilik Riwut Airport in Palangka Raya - Karyadi, Karyadi; Hestiana, Miftahul (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2016)
The purpose of the research is to explain and describe the Quality of Services for Making a Limited Security Entry Permit or Pass People Card at the Unit Office for the Tjilik Riwut Class I Airport in Palangka Raya. The type of research used in this study is descriptive with qualitative research methods. The type of data in this study is primary data, that is, from the officers making the Entrance Sign for Limited Security Area or Pas Card and the applicants. While secondary data comes from official documents related to this study such as SOP for Pas People. Techniques for collecting data using interviews, observation, and documentation. The focus of his research was the Making of Limited Security Area Entry Signs or Pass People Cards at Unit Offices Organizing the Tjilik Riwut Class I Airport in Palangka Raya. Based on the results of the study, the quality of service provided by the Office of the Unit Operator of Class I Tjilik Riwut Palangka Raya Airport is still not optimal, because of the five service quality indicators there are three indicators that have not run well, namely indicators of Tangibles, Reliability, and Empathy, while two indicators that have gone well are indicators of Responsiveness and Assurance